2011
DOI: 10.1136/hrt.2010.219568
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin, adiponectin and clinical course of acute fulminant myocarditis

Abstract: In patients with acute myocarditis, the plasma thioredoxin level was increased in the more severe form, and a reduced level of adiponectin was closely correlated with worse short-term outcome in patients with FM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Experimental studies indicated that Trx-1 overexpression protects against cardiac cell apoptosis and is associated with good cardiac function in animal models of HF [14,23]. Trx-1 is reportedly rapidly released into the circulation from the damaged cardiomyocytes [24,25], and is increased with advancing CHF severity [9]. Here we showed for the first time that plasma Trx-1 is an independent predictor of future cardiac events.…”
Section: Oxidative Stress and Heart Failuresupporting
confidence: 49%
“…Experimental studies indicated that Trx-1 overexpression protects against cardiac cell apoptosis and is associated with good cardiac function in animal models of HF [14,23]. Trx-1 is reportedly rapidly released into the circulation from the damaged cardiomyocytes [24,25], and is increased with advancing CHF severity [9]. Here we showed for the first time that plasma Trx-1 is an independent predictor of future cardiac events.…”
Section: Oxidative Stress and Heart Failuresupporting
confidence: 49%
“…In addition, severity of myocarditis, an inflammation of the heart most likely due to virus infection (395), is correlated to Trx1. In mouse models and patients, Trx1 was up-regulated in the acute stage (505,708) and enhanced in plasma in more severe forms of myocarditis, respectively (129,546). Temocapril treatment of rats in the beginning of experimental autoimmune myocarditis ameliorated the severity via up-regulation of Trx1 in the acute phase (858).…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…An investigation into the etiology of FM demonstrates disturbances in the immune system, overstimulation, and disrupted cytokines and chemokines profiles, is critical. 129 Upregulated cytokines or chemokines are the natural reaction against infection but a huge disturbance of immune homeostasis can lead to organ damage. Pro-inflammatory cytokines like IL-1, IL-6, CD-40, and TNF-α, as well as and anti-inflammatory cytokines including sTNFR and IL-10, are elevated in the serum of FM patients.…”
Section: Figmentioning
confidence: 99%